2012
DOI: 10.1093/toxsci/kfs263
|View full text |Cite
|
Sign up to set email alerts
|

Loss of A1 Adenosine Receptor Attenuates Alpha-naphthylisothiocyanate-Induced Cholestatic Liver Injury in Mice

Abstract: Cholestasis has limited therapeutic options and is associated with high morbidity and mortality. The A(1) adenosine receptor (A(1)AR) was postulated to participate in the pathogenesis of hepatic fibrosis induced by experimental extrahepatic cholestasis; however, the contribution of A(1)AR to intrahepatic cholestatic liver injury remains unknown. Here, we found that mice lacking A(1)AR were resistant to alpha-naphthyl isothiocyanate (ANIT)-induced liver injury, as evidenced by lower serum liver enzyme levels an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 40 publications
(40 reference statements)
1
15
0
Order By: Relevance
“…In contrast, renal mRNA level of Asbt was significantly down-regulated, accompanied by increased concentrations of bile acid and bilirubin in urine. These results indicated that adaptive responses to cholestasis also occur in the kidney in an effort to eliminate excess bile acids and toxic compounds from circulation which is according with previous report [29]. In addition, DNts pretreatment further increased the renal mRNA level of Ostβ in ANIT-intoxicated rats, accompanied by further increase in urinary excretion of bile acid and bilirubin (Figure  7).…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, renal mRNA level of Asbt was significantly down-regulated, accompanied by increased concentrations of bile acid and bilirubin in urine. These results indicated that adaptive responses to cholestasis also occur in the kidney in an effort to eliminate excess bile acids and toxic compounds from circulation which is according with previous report [29]. In addition, DNts pretreatment further increased the renal mRNA level of Ostβ in ANIT-intoxicated rats, accompanied by further increase in urinary excretion of bile acid and bilirubin (Figure  7).…”
Section: Discussionsupporting
confidence: 88%
“…Proteins were extracted following the procedure described previously. 50 The proteins were separated by SDS-PAGE on 8–12% polyacrylamide gels and subsequently electrically transferred to a PVDF membrane. After blocking with 5% (w/v) BSA in TBST at room temperature for 1 h, the membranes were then incubated with an appropriate specific primary antibody (anti-HA, 1 : 2000; anti-PPAR- γ , 1 : 1000; anti-PER1, 1 : 200; anti- β -actin, 1 : 1000) at 4 °C overnight, followed by incubation with an HRP-conjugated secondary antibody (1 : 10 000).…”
Section: Methodsmentioning
confidence: 99%
“…The receptor that seems to be mainly responsible for adenosine protection is A 2b AR 47, 48 . A 1 AR was also shown to have a protective effect against ethanol-induced hepatotoxicity 49 and to protect against alpha-naphthylisothiocyanate-induced cholestatic liver injury induced by DPCPX (a specific A 1 AR antagonist) in A 1 AR deficient mice 50 . A 2a AR is expressed by heptatic stellate cells, where it regulates fibrogenesis and contractility 51, 52 .…”
Section: Analysis Of Clinical and Epidemiological Datamentioning
confidence: 99%